2005
DOI: 10.1016/j.jtcvs.2004.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and differential changes in myocardial and plasma endothelin in patients undergoing cardiopulmonary bypass

Abstract: The unique findings of this study were 2-fold: First, significant compartmentalization of endothelin exists within the human myocardium. Second, a significantly higher and temporally disparate change in myocardial interstitial endothelin occurs during and after cardiopulmonary bypass when compared with systemic levels. These dynamic changes in myocardial endothelin likely influence coronary vascular tone and contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 27 publications
2
24
1
Order By: Relevance
“…12,15,20 Elegant studies by Spinale et al have demonstrated a 4-fold increase in myocardial interstitial ET-1 levels after cardiopulmonary bypass. 21 However, even at peak levels postoperatively, myocardial ET-1 levels were only 50 fmol/L and in plasma these levels were Ͻ20 fmol/L. At doses of 100 pmol/L, we observed no effect of ET-1 on cellular NO …”
Section: Effect Of Et-1 On No Productioncontrasting
confidence: 53%
“…12,15,20 Elegant studies by Spinale et al have demonstrated a 4-fold increase in myocardial interstitial ET-1 levels after cardiopulmonary bypass. 21 However, even at peak levels postoperatively, myocardial ET-1 levels were only 50 fmol/L and in plasma these levels were Ͻ20 fmol/L. At doses of 100 pmol/L, we observed no effect of ET-1 on cellular NO …”
Section: Effect Of Et-1 On No Productioncontrasting
confidence: 53%
“…Inhibition of the classical PKC isoforms (without exogenous ET-1) during CA improved myocyte shortening from CA only values. Because past studies have provided evidence that ET-1 levels increase within the myocardial interstitium during cardiopulmonary bypass 4,16 and that myocytes can synthesize and release ET-1, 7 incubation of myocytes with CA may have likely resulted in ET-1 production and subsequent PKC activation. Nevertheless, concomitant inhibition of each of the classical PKC isoforms in the presence of exogenous ET-1 and CA resulted in a marked improvement in myocyte shortening when compared with CA only.…”
Section: Discussionmentioning
confidence: 99%
“…Transient left ventricular (LV) dysfunction occurs after CA 1 and is associated with increased levels of bioactive peptides, including the vasoactive peptide, endothelin-1 (ET-1). [2][3][4] Moreover, elevated ET-1 levels in patients during and after cardiac surgery requiring CA may contribute to a complex postoperative course. 3 Although the effects of ET-1 on LV pump function after CA are likely to be multifactorial, ET-1 has been demonstrated to modulate myocyte contractile function, [5][6][7] which in turn can influence LV function.…”
mentioning
confidence: 99%
“…Further research demonstrated that the myocardial ECM maintains alignment of myofibrils within the myocyte through a collagen-integrincytoskeleton-myofibril relation (50,132,254,365,367,395,398,441). In addition to a fibrillar collagen network, a basement membrane, proteoglycans, and glycosaminoglycans, the myocardial ECM contains a large reservoir of bioactive molecules (17,34,41,64,89,95,101,109,111,114,188,288,360,362,492). For example, it has been demonstrated that the concentration of bioactive signaling molecules such as angiotensin II (ANG II) and endothelin (ET)-1 are over 100-fold higher within the myocardial interstitium than in plasma (89,101,288,492).…”
Section: A Structure and Function Of The Myocardial Matrixmentioning
confidence: 99%
“…In addition to a fibrillar collagen network, a basement membrane, proteoglycans, and glycosaminoglycans, the myocardial ECM contains a large reservoir of bioactive molecules (17,34,41,64,89,95,101,109,111,114,188,288,360,362,492). For example, it has been demonstrated that the concentration of bioactive signaling molecules such as angiotensin II (ANG II) and endothelin (ET)-1 are over 100-fold higher within the myocardial interstitium than in plasma (89,101,288,492). Moreover, cytokine activation and signaling such as that for tumor necrosis factor-␣ (TNF) is highly compartmentalized within the myocardial interstitium (95,111).…”
Section: A Structure and Function Of The Myocardial Matrixmentioning
confidence: 99%